(untitled) (Global Journal of Management and Business Research, 2023)
Though the use of Wearable Fitness Trackers WFT is advancing at an unprecedented pace in developed countries Bangladesh is still fall behind far away to cope with the proliferate features of advanced technologies whereas age differences play a vital role for technology adoption especially WFT devices in the context of developing countries Thus this study based on the factors used in Extended Unified Theory of Acceptance and Use of Technology UTAUT2 along with an additional construct Health consciousness explore the relationship among the endogenous and exogenous variables to develop a clear-foresightedness regarding the WFT adoption in Bangladesh To achieve this a survey was employed to collect primary data from 288 WFT users The data were analyzed using the Partial Least Squares PLS method a statistical analysis technique based upon Structural Equation Modeling SEM However this study explored that hedonic motivation health consciousness effort expectancy facilitating conditions habit as well as performance expectancy p 0 05 are the most cardinal factors that have a strong influence on behavioral intention of the users to adopt WFT devices Moreover the impact of effort expectancy habit health consciousness on intention-to-use of WFT is further multiplied the usage behavior by the virtue of the moderating effect of the age differences The study however revealed social influence and price value are trivial factors working as catalyst behind the acceptance of WFT devices p 0 05 Therefore the findings can guide the WFT marketers and policymakers to make some fruitful decisions for encouraging the usage of WFT devices considerably among the target population